Predictors of quality teaching in Makkah primary schools - Jusoh, Rosnani; Mlibari, Nada Abdul Raheem M. (Human Resource Management Academic Research Society, 2018)
The aim of this study is to examine the predictors of quality teaching in Makkah primary schools by examining the set of factors that influence Makkah primary school teachers. Based on Keller’s and Abraham Maslow’s theories of motivation, a model is developed and tested to examine teachers’ motivational factors to quality teaching. Five precursors (interest, relevance, expectation, satisfaction and self-actualisations) of quality teaching are presented in the model. The analysis procedure made use of descriptive statistics and bivariate correlation. The findings reveal that there is a reasonably high quality teaching among Makkah primary school teachers. In addition, the result indicated a significant positive relationship between the independent variables (interest, relevance and self-actualisation) and the dependent variable (quality of teaching). And found interest, relevance and self-actualisation as statistically significant predictors of quality teaching among Makkah primary school teachers.